Corporate Governance And Accounting Quality In Malaysia - Ooi, Chee Keong (2014)
Malaysia faces increased competition from countries in the region and from emerging economies such as India and China in attracting investors. It is not just the natural resources, quality of labour force and political stability that attract investors to its shores. Equally important is the accounting quality, its reliability, transparency and corporate governance. Therefore, the main objective of this research is to examine the changes in accounting quality before and after the implementation of Financial Reporting Standards (FRS) on January 1, 2006. This research also examines the relationship between various governance mechanisms of board structure, audit committees and accounting quality in Malaysia. This study will be conducted by using the entire main board public-listed companies (PLCs) as population for the year of 2003 to 2008 in order to obtain the sufficient samples for analysis. The final sample for this study comprised 397 non-financial companies with complete data for accounting quality and corporate governance variable. The overall results in this study find that accounting quality has reduced in terms of higher earnings management and lesser timely loss recognition during the post IFRS and post MCCG period. Furthermore, the results also suggest that corporate governance attributes of governance expertise in board committee, directors’ ownership, role duality or chairman independence, audit committee financial expertise, audit committee independence are associated at significant levels with accounting quality during the post IFRS and post MCCG period. Its results are useable by stock market participants in their evaluation of the roles of corporate governance and ownership structure in enhancing the quality of reported earnings. The findings will also help regulators to define effective corporate governance attributes and to assess the requirements for disclosure of corporate governance practices in future.